Economic and Social Transformation through Bank Sampah Berkah in Sumbersari, Sekampung District, East Lampung - Buchori Buchori; Hikmatul Aliyah; Putri Sandora; Prasetiyo Prasetiyo (Journal of Research in Social Science and Humanities, 2024)
Waste is a solid material that is a byproduct of human activities, which is no longer desired or needed. According to the World Health Organization (WHO), waste is defined as items from human activities that are no longer needed, used, or wanted, and thus discarded. Waste management includes all activities involved in handling waste from generation to final disposal, including waste minimization, collection, transfer and transportation, processing, and final disposal. In response to this issue, Bank Sampah Berkah in Sumbersari Village, Sekampung District, East Lampung Regency, has taken the initiative to address local waste problems. It is hoped that this waste bank can provide a solution to the existing waste issues. To date, Bank Sampah Berkah manages over 2 tons of waste per month.The research question addressed in this study is: “What is the impact of Bank Sampah Berkah (BSB) on the welfare of the community in Sumbersari Village, Sekampung District, East Lampung Regency?” This study is limited to one variable, which is community welfare, with the object of research being Bank Sampah Berkah. The study location is Sumbersari Village, Sekampung District, East Lampung Regency.The results of the study show that the calculated Chi-Square value is 320.07. Based on the 5% and 1% significance levels, the Chi-Square table values are 43.773 and 50.892, respectively. Thus, the calculated Chi-Square value is greater than the Chi-Square table values at both the 5% and 1% significance levels (43.773 320.07 50.892). This indicates that the presence of Bank Sampah Berkah in Sumbersari Village, Sekampung District, East Lampung Regency has a positive impact on improving community welfare.